2018
DOI: 10.3390/genes9070333
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-106a-5p Inhibited C2C12 Myogenesis via Targeting PIK3R1 and Modulating the PI3K/AKT Signaling

Abstract: The microRNA (miR)-17 family is widely expressed in mammalian tissues and play important roles in various physiological and pathological processes. Here, the functions of miR-106a-5p, a member of miR-17 family, were explored during myogenic differentiation in C2C12 cell line. First, miR-106a-5p was found to be relatively lower expressed in two-month skeletal muscle tissues and gradually decreased upon myogenic stimuli. Forced expression of miR-106a-5p significantly reduced the differentiation index, fusion ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Moreover, PIK3R1 expression is regulated by multiple miRNAs. For example, miR-198 and miR-106a-5p can target PIK3R1 to regulate cancer progression 34,35. The present study predicted and verified that PIK3R1 was a downstream target of miR-498.…”
supporting
confidence: 76%
“…Moreover, PIK3R1 expression is regulated by multiple miRNAs. For example, miR-198 and miR-106a-5p can target PIK3R1 to regulate cancer progression 34,35. The present study predicted and verified that PIK3R1 was a downstream target of miR-498.…”
supporting
confidence: 76%
“…Furthermore, PIK3R1 level is reduced by miR-16-5p, which inhibits cell cycle and enhances cell apoptosis by modulating of the PI3K/AKT/NF-KB pathway [41]. Besides, miR-495, miR-106a-5p, miR-455 and miR-15 were directly or indirectly contribute to the regulation of PIK3R1 expression [42,43]. In the present study, we demonstrated that miR-17-5p could bind to PIK3R1 3′UTR directly.…”
Section: Discussionmentioning
confidence: 51%
“…In siCDR1as pro les, the most enriched pathways of the downregulated mRNAs were (PI3K)-AKT signaling pathway, Focal adhesion, Rap1 signaling pathway, and MAPK signaling pathway. The downregulation of PI3K/AKT signaling pathway by miR-106a-5p was shown to inhibit myogenic differentiation of C2C12 myoblast [62]. Also, according to Jiang et al the knockdown of PI3-Kinase or its downstream target AKT prevents muscle differentiation in cell culture, while activation of PI3-Kinase and Akt induces myogenic differentiation [63,64].…”
Section: Discussionmentioning
confidence: 97%
“…Considering the knockdown of DICER1, we realized that the KEGG pathways of the downregulated mRNAs include PI3K-AKT signaling pathway [62], Focal adhesion [66], and ECM receptor interaction [66], which are also recognized to be associated with muscle development. Moreover, FoxO signaling pathway [66], MAPK signaling pathway [70], Rap1 signaling pathway [68,69], and mTOR signaling pathway [77] were also known to be associated with the upregulated miRNAs.…”
Section: Discussionmentioning
confidence: 99%